Single-Cell Sequencing Reveals the Novel Role of Ezh2 in NK Cell Maturation and Function - Yu, Minghang; Su, Ziyang; Huang, Xuefeng; Wang, Xi (Frontiers in Immunology, 2021)
Natural killer (NK) cells are lymphocytes primarily involved in innate immunity and exhibit important functional properties in antimicrobial and antitumoral responses. Our previous work indicated that the enhancer of zeste homolog 2 (Ezh2) is a negative regulator of early NK cell differentiation and function through trimethylation of histone H3 lysine 27 (H3K27me3). Here, we deleted Ezh2 from immature NK cells and downstream progeny to explore its role in NK cell maturation by single-cell RNA sequencing (scRNA-seq). We identified six distinct NK stages based on the transcriptional signature during NK cell maturation. Conditional deletion of Ezh2 in NK cells resulted in a maturation trajectory toward NK cell arrest in CD11b SP stage 5, which was clustered with genes related to the activating function of NK cells. Mechanistically, we speculated that Ezh2 plays a critical role in NK development by activating AP-1 family gene expression independent of PRC2 function. Our results implied a novel role for the Ezh2-AP-1-Klrg1 axis in altering the NK cell maturation trajectory and NK cell-mediated cytotoxicity.